fo009066: De 13 pioniers van Rochdale
"Zwart-witfoto van de 13 pioniers van Rochdale. Groepsfoto met v.l.n.r. James Standrino, John Bent, James Smithies, Charles Howarth, David Brooks, Benjamin Rudman, John Scowcroft, James Manock, John Collier, Samuel Ashworth, William Cooper, James Tweedale en Joseph Smith. Opschrift: Photograph of thirteen of the original members of the Rochdale Equitable Pioneers' Society. FULL TEXT AVAILABLE AT AMSAB-ISH"